Writing Spanish history in the global age: connections and entanglements in the nineteenth century. Issue 3 (31st October 2018) - Luengo, Jorge; Dalmau, Pol
Abstract: Modern Spain has remained largely absent from the debates and narratives of global history. In sharp contrast to the early modern period, the case of Spain in the nineteenth century has been overwhelmingly studied from regional and national perspectives. Fortunately, valuable efforts to integrate this country into wider frames of analysis have emerged in the last decade. Building on these writings, this article will argue that connections and entanglements represent two valuable perspectives, which allow the insertion of the Spanish experience into contemporary narratives of global history. The article has two aims. First, it seeks to 'decentre' modern Spain, by moving beyond its territorial borders within the Iberian Peninsula, and by examining its global dimensions, through connections with territories, colonies, and nations on several continents. Second, it aims to reveal valuable insights for current debates on global history, which arise from a focus on a country that is usually considered to have been both marginal and peripheral.